Waste Stabilization Ponds and Aerated Lagoons Performance in Removal of Wastewater Indicator Microorganisms - Seyed ali Ghasemi; Shahnaz Danesh (آب و فاضلاب, 2013)
In this work, the performance of two treatment plants in the City of Mashhad, one with an aerated lagoons system and the other one with waste stabilization ponds system were evaluated in regard to their efficiency in reduction of pathogenic microorganisms. For this purpose, over a period of one year (with 15-days intervals), samples were taken from the influent and effluent (prior to disinfection unit) of the above mentioned treatment plants. The samples then were analyzed for parameters such as temperature, pH, density of total coliforms (TC) and fecal coliforms (FC), dissolved oxygen and total suspended solids concentration. The results indicated that the aerated lagoons system was much more efficient in removal of indicator bacteria than the waste stabilization ponds during autumn and winter periods. However during the summer months, the waste stabilization ponds showed a higher efficiency in this regard. In general, the waste stabilization ponds system reduced the density of TC and FC by 0.21-2.15 log10 and 0.20-2.33 log10, respectively. In contrast, the levels of reduction in aerated lagoons system were in the range of 0.29-2.03 log10 for TC and 0.42-2.40 log10 for FC. Results indicated that solar intensity, pH and dissolved oxygen concentration were found to be the most significant parameters that reduced the microorganisms population in waste stabilization ponds, While, in the aerated lagoons system, the dissolved oxygen concentration in aerated basin and solar intensity play the most important role. In general, without receiving an adequate disinfection, the effluent from waste stabilization ponds and aerated lagoons cannot provide the microbiological standards required for irrigation of agricultural crops.